2021
DOI: 10.21037/apm-20-1528
|View full text |Cite
|
Sign up to set email alerts
|

The role of immunotherapy in combination with oligometastasis-directed therapy: a narrative review

Abstract: Metastatic disease is a significant cause of morbidity and mortality among patients with cancer.Patients with oligometastatic cancer represent a subset of the metastatic population with a limited amount of disease that has metastasized distantly and progresses at a slow pace and thus has the potential to be cured with metastasis-directed local therapy. Recent studies examining the role of metastasis-directed therapy in patients with oligometastatic disease have primarily focused upon treatment with ablative do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 142 publications
(163 reference statements)
0
5
0
Order By: Relevance
“…Combining ICB and SBRT aims to reduce immunosuppression and induce ICD in the TME, enhancing the anti-tumor immune response. However, prospective trials have not consistently shown significant efficacy improvements [ 18 ]. Implementing stricter selection criteria, like excluding patients with prior radiation at disease progression sites and ensuring optimal performance scores before treatment, may enhance response rates.…”
Section: Discussionmentioning
confidence: 99%
“…Combining ICB and SBRT aims to reduce immunosuppression and induce ICD in the TME, enhancing the anti-tumor immune response. However, prospective trials have not consistently shown significant efficacy improvements [ 18 ]. Implementing stricter selection criteria, like excluding patients with prior radiation at disease progression sites and ensuring optimal performance scores before treatment, may enhance response rates.…”
Section: Discussionmentioning
confidence: 99%
“…Despite adequate local treatment however, OMD patients have a propensity for failing distantly. 24 , 25 Moreover, the first-line SoC treatment for metastatic NSCLC has shifted from cytotoxic chemotherapy to upfront immunotherapy, chemo-immunotherapy, or targeted therapy. 26 For NSCLC patients with synchronous or metachronous OMD who are to receive immunotherapy upfront or at disease progression, it is imperative to carefully consider how and when SABR can be strategically incorporated into this treatment paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…This creates a form of radioresistance 39 which may be overcome by the administration of a concurrent PD-L1 antibody with RT. 24 , 40 ICI use in combination with RT therefore has the potential to address the challenges of pro-tumor microenvironment changes as well as tumor radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…It may well be that other diseases or novel agent combination under investigation in other phase III trials (NRG-LU002, COMET3, and CORE) will yield different outcomes. 9 For now, BR002 demonstrated that metastasis-specific local therapy for palliation remains the standard of care for breast cancer.…”
mentioning
confidence: 99%